The Pembelajaran STEAM Terhadap Keterampilan Proses Sains Ditinjau dari Sikap Ilmiah Mahasiswa pada Mata Kuliah Kajian Fisika Kejuruan - Fajrul Wahdi Ginting; Nimas Sri Rejeki; Agustina Miranda; Halimatus Sakdiah (Jurnal Penelitian Pendidikan IPA, 2022)
21st-century education requires students to have Science Process Skills (SPS) to be able to compete in the academic world and the industrial world 5.0. SPS itself is a skill needed to solve problems by following scientific stages. The application of the STEAM learning approach using the Project Based Learning (PjBL) learning model is expected to stimulate students to improve their skills. The research design used the One Group Pretest-Posttest Design. The instruments used were tests to observe SPS variables and non-tests to observe scientific attitudes. Hypothesis research analysis using one-way ANOVA analysis. The results of the study found that there was an effect of STEAM learning on student SPS and there were differences in student SPS that had high, medium, and low scientific attitudes.